Money demand and the role of monetary indicators in forecasting euro area inflation - Christian Dreger; Jürgen Wolters (FIW - Research Centre International Economics, 2013)
This paper examines the stability of money demand and the forecasting performance of a broad monetary aggregate (M3) in predicting euro area inflation. Excess liquidity is measured as the difference between the actual money stock and its fundamental value, the latter determined by a money demand function. The out-of sample forecasting performance is compared to widely used alternatives, such as the term structure of interest rates. The results indicate that the evolution of M3 is still in line with money demand even in the period of the financial and economic crisis. Monetary indi-cators are useful to predict inflation, if the forecasting equations are based on measures of excess liquidity.
Keywords: C22; C52; E41; 330; Money demand; excess liquidity; inflation forecasts